Mobile Teacher Professional Development (MTPD): Delving into English Teachers’ Beliefs in Indonesia - Saiful, Jepri Ali (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
In recent years, mobile phones have been used for teacher professional development (TPD). However, the potential use of smartphones, a current-generation of mobile phones, to develop teachers’ pedagogical, social, personal, and professional competences remains underexplored. This mixed methods study, examining the potential use of smartphones for TPD by delving into English teachers’ beliefs, employed a sequential explanatory approach. A quantitative survey was completed by 81 participants, followed by qualitative interviews with 8 selected participants. All the respondents were English teachers in elementary, junior, and senior high schools in 11 provinces in Indonesia. The survey was tested for validity and reliability, and analysed using the descriptive statistics method, while the semi-structured interview was analysed using the content analysis method. Almost all teachers had very favourable and favourable beliefs about the use of smartphones for TPD, perceiving that a smartphone could facilitate the enhancement of their pedagogical knowledge, communication skills, positive characters and English proficiency. Very few teachers had unfavourable beliefs, but among those who did, they believed traditional face-to-face TPD was more beneficial and that smartphones would only lead to addiction. This study recommends that smartphones be optimally applied by English teachers for TPD activities and that governments facilitate such implementation by constructing smartphone TPD models and applications.